GLASS: Global Lorlatinib for ALK(+) and ROS1(+) retrospective Study: real world data of 123 NSCLC patients - YUMUK, PERRAN FULDEN (ELSEVIER IRELAND LTD, 2020)
Lorlatinib is a third-generation tyrosine-kinases inhibitor (TKI) targeting ALK/ROS1 fusions. The FDA has approved lorlatinib for TKI-pretreated ALK(+) NSCLC, while its approval for ROS1( + ) is still pending. Here we present the largest real-world data of NSCLC patients harboring ALK/ROS1 rearrangements treated with lorlatinib. Methods: 123 patients were enrolled retrospectively (data cut-off 1/1/2019). Lorlatinib was administered through an early access program for patients with no other available therapy. Outcome and response were defined by each investigator upon RECIST 1.1 criteria. Results: 106 ALK(+) and 17 ROS1(+) patients recruited from 8 different countries. The ALK( + ) cohort included 50 % males, 73 % never-smokers and 68 % with brain metastases. Extracranial (EC) and intracranial (IC) response rates (RR) were 60 % and 62 %, with disease control rates (DCR) of 91 % and 88 % respectively. Mean duration of therapy (DoT) was 23.9 +/- 1.6 months and median overall survival (mOS) was 89.1 +/- 19.6 months. ROS1 cohort enrolled 53 % males, 65 % never-smokers and 65 % had brain metastases. EC and IC RR were 62 % and 67 % with DCR of 92 % and 78 % respectively. Median DoT was 18.1 +/- 2.5 months and mOS of 90.3 +/- 24.4 months. OS and DoT in both cohorts were not significantly correlated with line of therapy nor other parameters. The most common adverse events of any grade were peripheral edema (48 %), hyperlipidemia (47 %), weight gain (25 %) and fatigue (30 %). CNS adverse events such as cognitive effect of grade 1-2 were reported in 18 % of patients. Conclusion: Lorlatinib shows outstanding EC/IC efficacy in ALK/ROS1(+) NSCLC. The observed mOS of 89 +/- 19 months in ALK(+) NSCLC supports previous reports, while mOS from of 90 +/- 24 months is unprecedented for ROS1( + ) NSCLC.
Keywords: Lorlatinib; Real-world data; ALK; ROS1; CELL LUNG-CANCER; HYBRID CAPTURE; SINGLE-ARM; OPEN-LABEL; CRIZOTINIB; REARRANGEMENT; IMMUNOHISTOCHEMISTRY; MULTICENTER; CRITERIA; RET